Student's Perceptions on Gender Representation in "English for Nusantara" (A Critical Discourse Analysis Study) - Nessa Yuanita; Utami Rosalina; Virga Putra Darma (NextGen Education Review Journal, 2025)
The purpose of this research is to examine gender representation in the English for Nusantara textbook for Grade VIII and to explore students’ perceptions of these representations. The research method employed is a qualitative approach involving critical discourse analysis and semi-structured interviews. The analysis draws on Van Dijk’s Socio-cognitive Approach to examine how gender is represented semantically, syntactically, rhetorically, and visually. Data was collected from a criteria-based sample of two students at SMP Negeri 10 Cirebon, both of whom demonstrated strong English proficiency. The results showed revealed that male characters are predominantly represented in active, central roles across stories, visuals, and sentence structures.  In contrast, female characters tend to occupy background or passive roles and are often linked with emotional, domestic, or supportive functions. The use of language also shows a significant disparity in pronoun frequency and character traits, with males described using positive and dynamic adjectives, while females are more often associated with personal appearance and social limitations. The findings suggest that textbooks should strive for balanced portrayals to avoid reinforcing traditional gender stereotypes.